Infections after pediatric ambulatory surgery: Incidence and risk factors. (30th January 2019) - Gerber, Jeffrey S.; Ross, Rachael K.; Szymczak, Julia E.; Xiao, Rui; Localio, A. Russell; Grundmeier, Robert W.; Rettig, Susan L; Teszner, Eva; Canning, Doug A.; Coffin, Susan E.
Abstract: Objective: To describe the epidemiology of surgical site infections (SSIs) after pediatric ambulatory surgery. Design: Observational cohort study with 60 days follow-up after surgery. Setting: The study took place in 3 ambulatory surgical facilities (ASFs) and 1 hospital-based facility in a single pediatric healthcare network. Participants: Children <18 years undergoing ambulatory surgery were included in the study. Of 19, 777 eligible surgical encounters, 8, 502 patients were enrolled. Methods: Data were collected through parental interviews and from chart reviews. We assessed 2 outcomes: (1) National Healthcare Safety Network (NHSN)–defined SSI and (2) evidence of possible infection using a definition developed for this study. Results: We identified 21 NSHN SSIs for a rate of 2.5 SSIs per 1, 000 surgical encounters: 2.9 per 1, 000 at the hospital-based facility and 1.6 per 1, 000 at the ASFs. After restricting the search to procedures completed at both facilities and adjustment for patient demographics, there was no difference in the risk of NHSN SSI between the 2 types of facilities (odds ratio, 0.7; 95% confidence interval, 0.2–2.3). Within 60 days after surgery, 404 surgical patients had some or strong evidence of possible infection obtained from parental interview and/or chart review (rate, 48 SSIs per 1, 000 surgical encounters). Of 306 cases identified through parental interviews, 176 cases (57%) did not have chart documentation. In our multivariable analysis, older age and black race were associated with a reduced risk of possible infection. Conclusions: The rate of NHSN-defined SSI after pediatric ambulatory surgery was low, although a substantial additional burden of infectious morbidity related to surgery might not have been captured by standard surveillance strategies and definitions.